#### Answer

(b+c)a = ba + ca

#### Work Step by Step

(b + c)a = a(b+c)
Using the distributive property; a(b+c) = ab + ac
Using the commutative property; ab + ac = ba + ca
Therefore, (b+c) a = ba + ca

Published by
Prentice Hall

ISBN 10:
0133500403

ISBN 13:
978-0-13350-040-0

(b+c)a = ba + ca

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.